Willingness to pay for organic food in Argentina: evidence from a consumer survey - Rodríguez, Elsa Mirta M. (2007)
Most food markets do not count on complete information about food quality for consumers. Quality has become a key concept in the new approaches of the Demand Theory (Lancaster, 1966; Antle, 1999), and, therefore, food quality information has turned into a crucial factor when explaining the existing differences between demand profiles. Throughout these last years, organic agriculture has undergone a notorious expansion due, among other things, to the greater interest shown by consumers aware of food safety concerns involving real or potential quality risks perceptions. (Henson, 1996) This paper aims to estimate consumers' willingness to pay (WTP) for organic food products available in the Argentinean domestic market, with a view to providing useful evidence to the government, and thus gain support in the promotion of organic production, regulation processes and labelling programs. The Contingent Valuation Method (Hanemann, 1984) was selected to estimate WTP. Data derives from a food consumption survey conducted in Buenos Aires city in April 2005. The parameters estimates for the selected products were obtained by applying a Binomial Multiple Logistic Regression. The results indicate that Argentinean consumers are willing to pay a price premium to acquire better quality products. Indeed, this is conditioned by the effective prices in the domestic market, in which price premiums range from 6% to 200%, thereby restricting their acquisition. Besides, the scarce availability of these healthy products has also become another meaningful obstacle for domestic consumption expansion in Argentina.